The Relationship Between Concentration, Achievement Motivation, and Academic Stress in Tennis Student Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aiming to examinetherelationship between concentration, achievement motivation, and academic stress in tennis athletes. The problem raised is how concentration and motivation for achievement can affect the level of academic stress experienced by student athletes. The research method used is a quantitative approach with a correlation research design. The population of this study istennisathlete students registered at the university, with a sample of 35 students selected by purposive sampling. The instrument used to measure the variablesofconcentration, motivation to achieve, and academic stress is a questionnaire that has been testedforvalidity and reliability. The data collection technique was carried out through the distribution of questionnaire to respondents, while the data analysis technique used Pearson correlation tests and linear regression. The results showed that there was a significant negative relationship between concentration and academic stress (r = -0.48, p = 0.003), US well US between achievement motivation and academic stress (r = -0.52, p = 0.001). The regression model used showed that concentration and motivation for achievement could explain 49%ofthe variabilityofacademic stress. The conclusion of the study is that increased concentration and motivation to excel can reduce the academic stress experienced by college tennis athletes, which can help them in balancing academic and athletic demands.